Performance analysis of a subgrade with low load capacity reinforced with geogrid using the finite element method - Flores, Damaris (2023)
The presence of soft soils creates a serious problem for road construction. This is because the subgrade has a low CBR value, leading to deformations on the road surface that can affect its stability and durability. To initiate the performance evaluation, laboratory tests were conducted to determine the physical and mechanical properties of the subgrade. In order to establish the parameters considered for developing the steel box test model, the structure comprising the subgrade, geogrid, and base was subjected to cyclic loading using a hydraulic actuator. The reinforcement used between the subgrade and the base was the TX-160 geogrid. The model was subjected to a maximum pressure of 550 MPa using a hydraulic actuator with a contact radius of 200 mm, simulating the contact radius between the base and the wheel. The deformations generated in the unreinforced design under maximum pressure reached values of 68.89 mm, while the deformations in the design with geogrid reinforcement, placed between the base and the subgrade, were reduced by almost 90% to a value of 6.48 mm. Consequently, increasing the thickness of the base resulted in a reduction of subgrade deformation.